Neuroleptic-induced acute respiratory distress syndrome - Soriano, Francisco Garcia; Vianna, Elcio dos Santos Oliveira; Velasco, Irineu Tadeu (São Paulo Medical Journal, 2003)
CONTEXT: A case of neuroleptic malignant syndrome and acute respiratory distress syndrome is pre0sented and discussed with emphasis on the role of muscle relaxation, creatine kinase, and respiratory function tests. CASE REPORT: A 41-year-old man presented right otalgia and peripheral facial paralysis. A computed tomography scan of the skull showed a hyperdense area, 2 cm in diameter, in the pathway of the anterior intercommunicating cerebral artery. Preoperative examination revealed: pH 7.4, PaCO2 40 torr, PaO2 80 torr (room air), Hb 13.8 g/dl, blood urea nitrogen 3.2 mmol/l, and creatinine 90 µmol/l. The chest x-ray was normal. The patient had not eaten during the 12- hour period prior to anesthesia induction. Intravenous halothane, fentanyl 0.5 mg and droperidol 25 mg were used for anesthesia. After the first six hours, the PaO2 was 65 torr (normal PaCO2) with FiO2 50% (PaO2/FiO2 130), and remained at this level until the end of the operation 4 hours later, maintaining PaCO2 at 35 torr. A thrombosed aneurysm was detected and resected, and the ends of the artery were closed with clips. No vasospasm was present. This case illustrates that neuroleptic drugs can cause neuroleptic malignant syndrome associated with acute respiratory distress syndrome. Neuroleptic malignant syndrome is a disease that is difficult to diagnose. Acute respiratory distress syndrome is another manifestation of neuroleptic malignant syndrome that has not been recognized in previous reports: it may be produced by neuroleptic drugs independent of the manifestation of neuroleptic malignant syndrome. Some considerations regarding the cause and effect relationship between acute respiratory distress syndrome and neuroleptic drugs are discussed. Intensive care unit physicians should consider the possibility that patients receiving neuroleptic drugs could develop respiratory failure in the absence of other factors that might explain the syndrome.